On the microphthalmous Lathrobium Gravenhorst species of Turkey IV. Redescription of the male Lathrobium brignolii Bordoni, with description of a new species, and an updated key for the microphthalmous Lathrobium species of Turkey (Coleoptera: Staphylinidae: Paederinae) - Anlaş, Si̇nan (Zootaxa, 2023)
In this study, a new microphthalmous species of the genus Lathrobium s. str. from central northern Anatolia, Turkey is described and illustrated: Lathrobium orduense sp. n. (Ordu province). Taxonomy of Lathrobium brignolii Bordoni, 1980 is revised. Additional records of four Lathrobium species are reported. Distributions of the microphthalmous Lathrobium species in Anatolia are mapped. A supplement to a recently published key to the Turkish microphthalmous representatives of the genus Lathrobium is provided. A total of 11 microphthalmous species are now known from Turkey.